2015
DOI: 10.1007/s40097-014-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of W-doped ZnO nanocomposite as a new and efficient nanocatalyst for the synthesis of biscoumarins in water

Abstract: W-doped ZnO nanocomposite (W-ZnO) is easily prepared and characterized using a variety of techniques including XRD, TEM, BET, ICP-OES and SEM. This reagent can be used as an efficient and heterogeneous catalyst for the preparation of biscoumarins in water under mild conditions. Easy preparation of the catalyst, mild reaction conditions, easy work-up procedure, excellent yields and short reaction times are some of the advantages of this work. In addition, in this article and for the first time, the preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The applicability of this catalyst for the synthesis of biscoumarins under optimized reaction condition was investigated. It is noteworthy that protected aldehydes such as oximes, semicarbazones, and 1,1‐diacetates for the first time reacted efficiently with 4‐hydroxycoumarin in the presence of W‐ZnO within 1.2–3.6 h in high yields (Tables and , entry 25) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of this catalyst for the synthesis of biscoumarins under optimized reaction condition was investigated. It is noteworthy that protected aldehydes such as oximes, semicarbazones, and 1,1‐diacetates for the first time reacted efficiently with 4‐hydroxycoumarin in the presence of W‐ZnO within 1.2–3.6 h in high yields (Tables and , entry 25) …”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that protected aldehydes such as oximes, semicarbazones, and 1,1-diacetates for the first time reacted efficiently with 4-hydroxycoumarin in the presence of W-ZnO within 1.2-3.6 h in high yields (Tables 1 and 2, entry 25). 40 TiO 2 NPs (5 mol%) catalyzed the synthesis of biscoumarins in water under reflux condition. After investigation of different amounts of the catalyst, solvents, and temperatures, the optimized reaction condition was obtained ( Table 1, entry 26).…”
mentioning
confidence: 99%
“…The suitability of this catalyst and exhaustive literature survey for the synthesis of coumarin derivatives inspired us to search the applicability of this catalyst for the synthesis of biscoumarins. The literature studies showed their synthesis using different methods such as catalyst‐free microwave‐assisted organic synthesis, 28 [PSebim][OTf], 29 propane‐1,2,3‐triyl tris(hydrogen sulfate), 30 phospho sulfonic acid, 31 W‐doped ZnO nanocomposite, 32 choline hydroxide, 33 o ‐benzenedisulfonimide, 34 P4VPy‐CuO‐NPs, 35 sulfonated rice husk ash, 36 piperidine, 37 magnetite‐containing sulfonated polyacrylamide, 38 CuO‐CeO 2 nanocomposite, 39 Montmorillonite K10·Ni0‐Mont, 40 taurine, 41 VB1, 42 cerric ammonium nitrate, 43 HY‐Zeolite, 44 FeNi 3 ‐ILs nanoparticles, 45 and so on and high yields were obtained. A comprehensive review on the synthesis of biscoumarin derivatives has recently been published 46 and it was found that the reported methods have their own merits coupled with endure drawbacks, that is, costly, tedious work up procedures, formation of toxic by‐products, use of toxic solvents, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The main method for the preparation of biscomarin derivatives is the Knoevenagel‐Michael reaction. Because of the importance of biscoumarins essentially bis(4‐hydroxycoumarin) in the mentioned fields, many catalysts in various conditions have been introduced for the preparation of them such as [bmim]BF 4 , SDS, [PSebim][OTf], propane‐1,2,3‐triyl tris(hydrogen sulfate), [pyridine–SO 3 H]Cl, phospho sulfonic acid, cellulose sulfonic, W‐doped ZnO nanocomposite, Bi(NO 3 ) 3 ⋅5H 2 O, choline hydroxide, o ‐benzenedisulfonimide, P 4 VPy–CuO‐NPs, sulfonated rice husk ash, silica‐Bonded N ‐propylpiperazine sodium n ‐propionate, boron‐sulfuric acid Nanoparticles, P 4 VPy‐BuSO 3 H−X(AlCl 3 ), 4‐(dimethylamino)pyridine, and piperidine …”
Section: Introductionmentioning
confidence: 99%